Hermeneutics in the Study of Tafseer Alquran: Understanding the Text and Context - Putri, Mirna; Zahara, Rani; Saudiah, Paridatus; Ediz, M. Hidayat; Fakhruddin, Fathiyah Mohd (LP2M STAI Balaiselasa YPPTI Pesisir Selatan Sumatera Barat, 2024)
This research discusses hermeneutics in the study of Alquran interpretation. The aim of this research is to understand the meaning of the text and context in interpreting the Alquran properly and correctly and making the understanding more comprehensive and accurate as well as its application in the current context. This research uses qualitative methods with a thematic analysis approach. By examining books, journals, research reports, magazines, tafsir books and other literature that discusses hermeneutics and interpretation of the Alquran. Then it is analyzed thematically based on the explanations contained in the interpretive books of the mufassir. Furthermore, to strengthen the analysis and discussion, the author also refers to expert opinions and various findings from previous researchers regarding this issue and topic. The result of this research is that we can understand the Alquran both in terms of the text and its context because the text cannot be separated from the context in which the text is expressed. To understand this, several rules are needed for understanding text and context. Among them you need to understand Asbab an-Nuzul, which is the specific background behind the revelation of a verse or chapter is also important to understand the text as a whole. Second, draft munasabah helps find connections and harmony between various verses. Third, draft nasikh mansukh highlighting changes and developments in understanding over time. This discussion is very important to discuss in contemporary times to help provide a deeper understanding of the study of Alquran interpretation and bring it to the present.